2005
DOI: 10.1029/2004gl022136
|View full text |Cite
|
Sign up to set email alerts
|

Radar investigations of low‐altitude quasi‐periodic echoes in Chung‐Li

Abstract: [1] Quasi-periodic (QP) radar echoes from the sporadic E-layers are also found at altitudes below 100 km which we call Low-altitude Quasi-Periodic echoes (LQP). We have used the Chung-Li VHF radar to study correct locations of these echoes creating irregularities, which are confined to the height range between 90 km and 100 km, have a thickness of 2 -4 km and are only slowly descending in altitude. They occur with periods of some tens of seconds to maximum three minutes. Since Chung-Li is close to the equatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Considering the finite beam width and the uncertainty in the time delay measurements, Patra et al [2002] estimated that the height ambiguity of the LQP echoes could be 550 m. In order to determine this more accurately, however, we need to have interferometry measurements, which is not available at this moment. It is worth mentioning that Pan et al [2005] showed the LQP echoes observed from 95–100 km to be localized within ±1° with respect to the magnetic field, indicating their strong aspect sensitive properties. We also rule out the possibility that the low altitude echoes may be due to signal leakage through azimuthal side lobes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Considering the finite beam width and the uncertainty in the time delay measurements, Patra et al [2002] estimated that the height ambiguity of the LQP echoes could be 550 m. In order to determine this more accurately, however, we need to have interferometry measurements, which is not available at this moment. It is worth mentioning that Pan et al [2005] showed the LQP echoes observed from 95–100 km to be localized within ±1° with respect to the magnetic field, indicating their strong aspect sensitive properties. We also rule out the possibility that the low altitude echoes may be due to signal leakage through azimuthal side lobes.…”
Section: Discussionmentioning
confidence: 87%
“…These echoes are commonly known as low‐altitude quasi‐periodic (LQP) echoes. When plotted in the range/height‐time intensity format, they display slanted striation‐like structures with periods of a few tens of seconds to 4 min [ Urbina et al , 2000; Rao et al , 2000; Patra et al , 2002; Sripathi et al , 2003; Pan et al , 2005; Patra et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Patra et al [2006] showed an LQP event occurring for more than 7 h and the echoes at the end of the run extended to as low as 87 km in altitude. Pan et al [2005], using the Chung‐Li radar (24.9°N, 121.2°E, 13.3°N magnetic latitude) in Taiwan, observed these echoes to occur in the height region of 96–100 km with a period of a few tens of seconds to 3 min.…”
Section: Introductionmentioning
confidence: 99%
“…Now we know that QP echoes are observed also from altitudes well below 100 km and these echoes have been reported from both middle and low latitudes [ Urbina et al , 2000; Rao et al , 2000; Patra et al , 2002; Pan and Rao , 2002; Sripathi et al , 2003; Pan et al , 2005; Patra et al , 2006]. Because of their occurrence at lower altitudes, they have been stamped as low‐altitude QP (LQP) echoes to distinguish them from the well‐known and much investigated QP echoes occurring above 100 km.…”
Section: Introductionmentioning
confidence: 99%